PS 14-88 BLOOD PRESSURE PREDICTS NEW-ONSET CHRONIC KIDNEY DISEASE INDEPENDENTLY OF METABOLIC SYNDROME – LONGITUDINAL DATA FROM THE CROATIAN RURAL STUDY (ENAH). (September 2016) - Ivkovic, Vanja; Vrdoljak, Ana; Karanovic, Sandra; Dika, Živka; Vukovic, Ivana; Kos, Jelena; Laganovic, Mario; Vrkic, Tajana Zeljkovic; Prlic, Margareta Fistrek; Pecin, Ivan; Jelakovic, Bojan
Abstract : Objective: Chronic kidney disease (CKD) and metabolic syndrome (MetSy) are important predictors of mortality. Our objective was to assess the predictors of new onset CKD in rural population with and without MetSy. Design and Method: Out of 954 subjects enrolled in ENAH follow-up study, 521 (147 m, 374 w) were eligible for further analysis and followed up for total of 3333 person-years (median 7 (5–7) years). Exclusion criteria were pregnancy, CV or cerebrovascular incident and chronic terminal diseases. Blood pressure (BP) was measured using Omron M6. Fasting blood was analysed for glucose, lipids, serum creatinine and other parameters. MetSy was diagnosed according to NCEP-ATP III criteria. Results: Prevalence of MetSy at baseline was 24.0% being similar in men and women (24.6% vs. 22.4%, p = 0.35). The prevalence of individual MetSy components in subjects with MetSy were: high BP (88.9%), pathological WC (81.6%), high FBG (60.0%), high TG (48.8%) and low HDL-C (30.4%); women having pathological WC more frequently (98.9% vs. 87.9%, p = 0.017). The incidence rate of new onset MetSy was 3.7% per year. Prevalence of CKD at baseline in our group was 5.6%, being similar in subjects with MetSy and controls (8.1% vs 5.1%, p = 0.13). Contrary to this, 31 subjects developed new onset CKD for an incidence rate of 1.0% per year and an incidence almost 2.5-fold higher in subjects with MetSy (11.5% vs. 4.8%, p = 0.02). There was no difference in number of MetSy components or their individual prevalence between CKD and non-CKD subjects (p > 0.05). In whole group, BP (OR 3.0, 95% CI 0.9, 10.0) and older age (OR 1.2, 95% CI 1.1, 1.3) were predictors of new onset CKD. Conclusions: MetSy is highly prevalent in Croatian rural population and frequently associated with CKD. Beside age, BP is predictor of new-onset CKD. Dietary and BP lowering population-level strategies might show efficient in preventing not just MetSy, but to a certain extent CKD.